Design for additive manufacturing: A three layered conceptual framework for knowledge-based design. (July 2023) - Haruna, Auwal; Yang, Maolin; Jiang, Pingyu
Designers face new challenges in the conceptual design phase because of the wide-ranging industrial application of additive manufacturing (AM). Structure simplification and function integration should be investigated during the conceptual design phase to embrace the design freedom that design for additive manufacturing (DFAM) offers. In this regard, a three-layered DFAM framework for knowledge-based design is established in this paper. The first layer utilizes a customized Gero's function-behavior-structure (FBS) model to support the extraction of DFAM knowledge. The second layer uses a knowledge graph (KG) approach to express the DFAM knowledge. The third layer focuses on applying KG for DFAM by providing design guidance during the conceptual design phase. The framework supports learning to capture, design feature guidelines, representation of design behavior, and interaction with AM design engineers. Thereby, the framework provides a well-ordered and coherent approach to exploit the buried new design advantages of AM during the conceptual design phase. Subsequently, to verify the feasibility of the framework in the design process, a prototype software system and a throttle pedal design project are used for demonstration.